Hydrochemistry of the Guarani Aquifer System modulated by mixing with underlying and overlying hydrostratigraphic units - Teramoto, Elias Hideo [UNESP]; Gonçalves, Roger Dias [UNESP]; Chang, Hung K. [UNESP] (Elsevier, 2020)
Study region: São Paulo State, Southeastern, Brazil. Study focus: Several studies were conducted on the Guarani Aquifer System (GAS), with as main focus the identification of major stratigraphic units and hydrodynamic properties governing groundwater flow. Geochemical assessment studies of the GAS focused on hydrochemical and isotopic characterization. Current understanding is that progressive rock–water interactions control the observed hydrochemical zonation. New hydrological insights for the region: Based on available analyses of the overlying Serra Geral Aquifer System (SGAS) and the deeper Permian Aquifer System (PAS), along with numerical simulation of mixing processes, we concluded that the hydrochemistry of the GAS is modulated by its mixing with groundwater inputs from overlying and underlying aquifers. Importantly, our work indicates that >50 % of the Guarani Aquifer System groundwater recharge in São Paulo State comes from Serra Geral Aquifer System seepage. This finding has critical implications regarding groundwater management, mass-balance calculations and estimations of groundwater residence times.
Keywords: Groundwater mixing; Guarani Aquifer System; Hydrochemical facies